The Most Frequent Agronomic Practices Used by the Coconut Farmers in the “Coconut Triangle” of Sri Lanka - Legrand, Baptiste; Perraut, Angélique; Herath, Chaminda; Wijekoon, Rusitha; Perera, Lalith (International Coconut Community, 2018)
The study was carried out to identify the most frequently practiced cultural practices by coconut growers in the main coconut growing area termed as “Coconut Triangle”, among a set of technical practices recommended by the Coconut Research Institute of Sri Lanka (CRISL). The objective was also to analyse the impact of these practices to the yield and to analyse the effects of the information sources to the growers to enhance the farmers skills. The study was carried out between June 2018 and August 2018. For the data collection, a questionnaire developed by CRISL was used and 62 growers were randomly selected. All the answers were gathered in a table file. Then, the data were analysed using tabular analysis and the software SPSS. The study reveals that most of the growers are having intercrops between the coconut trees, in large or very small scale even if the yield is lowand needs more space. For the soil moisture conservation around the coconut palm, the majority of the growers use the simple and low-cost technique; mulching around the coconut palms. However, 30.1% of the growers were found to not use any technique to improve the soil moisture even when the drought is a frequent event in the country, but this more valid for small scale growers. To improve their yield, majority of the growers preferred and used CRISL recommended coconut fertilizer mixture (Adult Palm Mixture or APM) over the other commercially available fertilizer mixtures. Finally, the study shows that farmers with large estates are the most involved to follow training programs and apply the advices given by the CRISL.